Protection of Fundamental Rights in the context of Surrogacy: A review of the recent case law of the European Court of Human Rights - Radovanović, Marina (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Surrogate motherhood is one of the most ethically sensitive phenomena today. Different views of the nature, purpose and consequences of surrogate motherhood lead to differences regarding political and legal regulation of surrogacy at the level of the states. As a consequence, couples who decide for this type of assisted parenting are often forced to carry out the entire procedure outside the territory of their home country. Thus, the phenomenon itself takes on the characteristics of a transnational one, creating a complex ground for the protection of human rights, primarily the rights of children who are born under conditions of surrogate motherhood. Consequently, national courts are forced to weigh between the prohibition of surrogacy and the protection of public safety, on the one hand, and the protection of the best interests of the child, on the other. The circle, however, does not close in the field of national jurisdictions. Thus, the agenda of the European Court of Human Rights increasingly includes delicate applications related to the protection of private and family life in the light of surrogate motherhood. This research will be centred around two such recent cases, providing a framework for understanding a kind of continuity in the reasoning of the European Court of Human Rights in this domain, but also for identifying new focal issues that will inevitably follow the modalities of contemporary transnational surrogacy. Keywords: fundamental rights, European Court of Human Rights, surrogate motherhood, respect for private and family life, best interest of the child, human dignity, non-discrimination.